Conceptualising nurse-patient therapeutic engagement on acute mental health wards: An integrative review. (May 2019) - McAllister, Sarah; Robert, Glenn; Tsianakas, Vicki; McCrae, Niall
Abstract: Objectives: The review aimed to 1) explore the constituents of nurse-patient therapeutic engagement on acute mental health wards; 2) map factors that influence engagement to the Theoretical Domains Framework and 3) integrate results into a conceptual model of engagement to inform the development of interventions to improve engagement. Design: A systematic integrative review using an established framework specific to the integrative review methodology. Data sources: Database searches (CINAHL, PsycINFO, BNI and Cochrane Library) and hand searching identified 3414 articles. After screening, applying eligibility criteria, and quality appraisal, 37 articles were included: n  = 27 empirical research studies, n  = 10 expert opinion pieces, n  = 1 case study and n  = 1 theoretical report. Review methods: Peer-reviewed empirical studies, theoretical reports or expert opinion pieces that explored therapeutic engagement as a stated aim and were conducted in acute mental health inpatient settings from the patient or nurse perspective were included. Data were extracted from the introduction, results and discussion sections of empirical research, and the complete article of theoretical and expert opinion pieces. Data were coded then grouped into subthemes and themes. Data relating to influencing factors were further categorised according to the Theoretical Domains Framework. Results were synthesised into a conceptual model of engagement. Results: Five conceptually distinct, but closely related constructs of engagement – called the "Principles of Engagement" – emerged: 1) Understanding the person and their experiences; 2) Facilitating growth; 3) Therapeutic use of self; 4) Choosing the right approach and 5) Authoritative vs. emotional containment. Influences on engagement ranged across all 14 theoretical domains of the Theoretical Domains Framework. Conclusion: A holistic understanding of the essential components of engagement may make it easier for nurses to recognise what they do, and to do it well. The model can be used to generate testable hypotheses about how and where to target behavioural change interventions. The Principles of Engagement must be reflected in the development of interventions to improve engagement.